2019
DOI: 10.1017/jfm.2019.635
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian coherent structures and entrainment near the turbulent/non-turbulent interface of a gravity current

Abstract: In this paper, we employ Lagrangian coherent structures (LCSs) theory for the threedimensional vortex eduction and investigate the effect of large-scale vortical structures on the turbulent/non-turbulent interface (TNTI) and entrainment of a gravity current. The gravity current is realized experimentally and different levels of stratification are examined. For flow measurements, we use a multivolume three-dimensional particle tracking velocimetry technique. To identify vortical LCSs (VLCSs), a fully automated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
(110 reference statements)
3
20
0
Order By: Relevance
“…Lagrangian methods are, however, not necessarily constrained by such requirements (Schlueter-Kuck and Dabiri 2017). This last feature drives the development of new post-processing strategies for the detection of coherent structures with data obtained from large-scale applications (Neamtu-Halic et al 2019;Wei et al 2019). Lagrangian (trajectory-based) analysis allows for improved understanding of various processes that take place in the ocean, atmosphere and even in the lab, among other problems, which often suffer from poor spatial resolution (Mathur et al 2019).…”
Section: List Of Symbols R Ijmentioning
confidence: 99%
“…Lagrangian methods are, however, not necessarily constrained by such requirements (Schlueter-Kuck and Dabiri 2017). This last feature drives the development of new post-processing strategies for the detection of coherent structures with data obtained from large-scale applications (Neamtu-Halic et al 2019;Wei et al 2019). Lagrangian (trajectory-based) analysis allows for improved understanding of various processes that take place in the ocean, atmosphere and even in the lab, among other problems, which often suffer from poor spatial resolution (Mathur et al 2019).…”
Section: List Of Symbols R Ijmentioning
confidence: 99%
“…Moreover, others only considered a small volume limited to the current/ambient interface ( 4 × 4 × 2 cm from a domain 200 × 50 × 50 cm) (Krug et al 2015). In the same experimental domain, Neamtu-Halic et al(2019) identified vortical Lagrangian coherent structures in the flow body capable of affecting the height of the turbulent/non-turbulent interface, though measurements were again limited to the current-ambient interface (this work considering 4 regions of 9 × 9 × 4 cm) precluding identification of structures lower in the flow. As a result of the limitations of these works, significant questions regarding the structure of the gravity current body remain.…”
Section: Introductionmentioning
confidence: 99%
“…The goal is to understand the impact of vortical structures as extracted from the flow on the dynamics of enstrophy near the TNTI. To identify the OECSs that are in proximity of the TNTI and to investigate their contribution to enstrophy and scalar transport, we use a recently developed conditional analysis by Neamtu-Halic et al [36].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it is widely accepted that entrainment rate reduces with increasing stratification as a consequence of the reduction of both the local entrainment velocity and the area of the TNTI [31,46,47]. Recently, Neamtu-Halic et al [36] used experimental data of a gravity current to show that OECSs modulate the area of the TNTI and that their modulating capacity diminish with increasing stratification. Moreover, OECSs have been observed to organize the flow field on the TNTI proximity thereby imposing the local entrainment velocity [36] and setting the mechanism that produces/destroys the surface area of the nearby TNTI [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation